Fiscal consolidation policies in the context of Italy's two recessions - Francesco Figari; Carlo Fiorio (University of Essex, Institute for Social and Economic Research (ISER), 2015)
The Italian Great Recession has a double-dip pattern. After the start of the global financial crisis, Italy experienced a second serious recession in 2011 because of the sovereign debt crisis. The reaction of Italian governments was mild at the beginning and more convinced since the start of the sovereign debt crisis in 2011. Adopted policies contributed to realign public finances at a sustainable level, while household real income decreased by 13 per cent and quite unevenly along the household income distribution. The medium-term outlook is still uncertain: a great deal depends on the capacity of the Italian economy to reduce the level of public debt and to return to sustained economic growth, which has been very weak for more than a decade.
Keywords: H12; H62; H63; H68; H50; I31; 330; Great Recession; Italy; net borrowing; debt; microsimulation; public finance